Analisis Tindak Tutur Ilokusi dan Prinsip Saling Tenggang Rasa (PSTR) dalam Stand up Comedy Raditya Dika - Dian Syahfitri (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2018)
Stand up Comedy is an artful comedy which is individually delivered directly in front of the spectators. Further, Stand up Comedy is part of humor. This research is purposed to describe the types of speech act illocution including with the Principle of Mutual Consideration (PMC) realized within the Stand up Comedy delivered by Raditya Dika. He is a writer and also known as a comic. Some phases of methods were conducted in completing the research; gathering the data, analyzing the data based on its function through contextual method. Then, data were studied and analyzed by conducting pragmatics theories those were theory of speech act and PMC. Based on the analysis, the utterances within Stand up Comedy delivered by Raditya Dika can be concluded into some significant findings, namely illocutionary speech acts were found that consists of five kinds of speech acts; representative, directive, expressive, comissive, and declarative. Moreover, PMC in the form of harm potential was also found in the analysis.